2019
DOI: 10.1029/2018gl081514
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Bomb 14C Into the Deepest Ocean Trench

Abstract: The food source of hadal endemic fauna provides an insight into the carbon cycle in trenches and a biological adaptation to the impoverished and harsh trench environment. Here, we present the first Δ14C results of hadal amphipods from three trenches in the Pacific to define the organic matter source in these remote ecosystems. Amphipod muscle tissues contain a bomb 14C signature (Δ14C from 10 ± 2‰ to 65 ± 2‰), thereby revealing a dietary preference for labile and fresh organic matter derived from the surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Hg isotope ratios of snailfish and amphipods from 6,000 to 10,250-m depth in the Mariana and Kermadec hadal trenches were measured and compared with Hg isotope measurements of a wide range of fish species in the central Pacific that feed at depths of 10–1,000 m. Based on odd-MIF and even-MIF isotopic signatures we conclude that the majority of Hg in the tissues of animals living in the hadal zone originates from the atmosphere, is methylated in the epipelagic (upper 200 m) and mesopelagic (200–1,000-m) zones, and is then delivered to the hadal zone (6,000–11,000 m) by the carcasses of fish, and to a lesser extent by particles ( 33 ). A near-surface source of Hg to hadal biota is consistent with recent documentation of “bomb 14 C” ( 59 ), lead ( 60 ), and persistent organic pollutants ( 61 ) in hadal biota. The importance of carrion to trench foodwebs is consistent with observations of seafloor communities of fish and amphipods that depend upon carrion for nutrition in other deep-sea regions (e.g., refs.…”
Section: Resultssupporting
confidence: 84%
“…Hg isotope ratios of snailfish and amphipods from 6,000 to 10,250-m depth in the Mariana and Kermadec hadal trenches were measured and compared with Hg isotope measurements of a wide range of fish species in the central Pacific that feed at depths of 10–1,000 m. Based on odd-MIF and even-MIF isotopic signatures we conclude that the majority of Hg in the tissues of animals living in the hadal zone originates from the atmosphere, is methylated in the epipelagic (upper 200 m) and mesopelagic (200–1,000-m) zones, and is then delivered to the hadal zone (6,000–11,000 m) by the carcasses of fish, and to a lesser extent by particles ( 33 ). A near-surface source of Hg to hadal biota is consistent with recent documentation of “bomb 14 C” ( 59 ), lead ( 60 ), and persistent organic pollutants ( 61 ) in hadal biota. The importance of carrion to trench foodwebs is consistent with observations of seafloor communities of fish and amphipods that depend upon carrion for nutrition in other deep-sea regions (e.g., refs.…”
Section: Resultssupporting
confidence: 84%
“…2) 6,7 . A study on amphipods from the Mariana Trench and two other Pacific trenches revealed that the bomb 14 C signals of the surface ocean could rapidly penetrate into the deepest ocean via fast sinking of surface POM 56 . It is thus likely that, similar to IHg(II), the MMHg produced in the surface and intermediate waters above the trenches transfers to the deep ocean through sinking of surface POM as well.…”
Section: Discussionmentioning
confidence: 99%
“…In 1963, the Nuclear Test Ban Treaty effectively limited atmospheric testing with the exception of a few dozen smaller yield detonations that occurred primarily in China and Africa in the 1960s and 1970s 1 . The presence of radioactive pollution from nuclear testing is globally ubiquitous, and detectable on every continent and even in deep ocean trenches 4 . Earth scientists widely apply the “bomb spike” radionuclides as a global chronological marker based on the assumption of strong radionuclide associations with minerals, and there are thousands of published studies using weapons fallout to trace soil transport and for dating sediments deposited in the 1960s 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%